2011
DOI: 10.1159/000325576
|View full text |Cite
|
Sign up to set email alerts
|

Milk and Growth in Children: Effects of Whey and Casein

Abstract: Consumption of cow's milk is recommended in many countries. Observational and intervention studies show that cow's milk most likely has a positive influence on growth in children. The strongest evidence comes from observational studies and intervention studies in low-income countries, but there are also observational studies from high-income countries showing positive associations between milk intake and growth. Milk seems thus to have a specific stimulating effect on linear growth, not only in developing coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
2
34
0
1
Order By: Relevance
“…Whey-dominant formulae have a whey-to-casein ratio (60:40) similar to that of human milk in early lactation [29]. Whey has a slightly higher protein quality (protein digestibility-corrected amino acid score) than casein and is more easily digested by the gastrointestinal system [30]. Similar effects of higher whey-to-casein ratios on EE are observed with greater contents of intact whey [12,13,15] or fully hydrolyzed whey [17].…”
Section: Discussionmentioning
confidence: 99%
“…Whey-dominant formulae have a whey-to-casein ratio (60:40) similar to that of human milk in early lactation [29]. Whey has a slightly higher protein quality (protein digestibility-corrected amino acid score) than casein and is more easily digested by the gastrointestinal system [30]. Similar effects of higher whey-to-casein ratios on EE are observed with greater contents of intact whey [12,13,15] or fully hydrolyzed whey [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the importance of milk in the diets of children concluded that dairy product intake is associated with better linear growth and bone development during childhood [26], even in wealthier countries with a high usual intake of milk [28]. Milk contains bioactive factors and stimulates insulin-like growth factor I and insulin synthesis, and peptides which can stimulate growth [29]. Milk is also a good vehicle for micronutrient fortification [26].…”
Section: The Importance Of Milk For Infants and Childrenmentioning
confidence: 99%
“…; Dror & Allen ; Mølgaard et al . ). However, the minimum amount of milk required to stimulate growth is unknown (Michaelsen et al .…”
Section: Considerations For Selecting Ingredientsmentioning
confidence: 97%
“…Inclusion of milk products (generally DSM powder, but sometimes whey protein concentrate or sweet whey) also reflects the hypothesis that milk has a positive impact on linear growth, which is supported by some evidence (Mølgaard et al . ). Milk provides high‐quality protein and several nutrients that are essential for growth, in highly bioavailable form.…”
Section: Considerations For Selecting Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation